Immigration and provision of public goods: Evidence at the local level in the U.S. - Anna Maria Mayda; Mine Zeynep Senses; Walter Steingress (Bank of Canada, 2023)
Using U.S. county-level data from 1990 to 2010, we study the causal impact of immigration on the provision of local public goods. We uncover substantial heterogeneity across immigrants with different skills, mainly due to the asymmetric impact immigrants have on the per capita tax base and local revenues. In the absence of full insurance through intergovernmental transfers, the changes in per capita revenues are reflected in changes in the provision of local public services: per capita public expenditures decrease with the arrival of low-skilled immigrants and increase with the arrival of high-skilled immigrants. While the two types of immigrants offset each other on average, spatial differences in the population shares of low-and high-skilled immigrants lead to unequal fiscal effects across U.S. counties. We find the estimated impact to differ across various public services and for second-generation immigrants.
Keywords: F22; H41; H7; J61; J68; R5; 330; Fiscal policy; International topics; Regional economic developments